0070 A Mexican Spanish Version of the Brief Index of Sleep Control. (25th May 2022) - Begay, Tommy; Valencia, Dora; Granados, Karla; Delgadillo, Marcos; Ghani, Sadia; Molina, Patricia; Alfonso-Miller, Pamela; Wills, Chloe; Grandner, Michael
Abstract: Introduction: The Brief Index of Sleep Control (BRISC) is a 4-item assessment of the degree to which an individual perceives that they are in control of their sleep. Previous work shows that this measure may be useful for sleep health promotion efforts. The present study describes an attempt to develop a version of this measure in Spanish, particularly for individuals of Mexican descent. Methods: Data were collected from a sample of N=100 individuals of Mexican Descent in Nogales, Arizona, located at the US-Mexico border. The BRISC is a 4-item scale that quantifies the degree to which an individual perceives that their sleep is under their control, assessing perceived control over time to bed, time out of bed, total sleep time, and sleep quality. To translate the measure into Spanish, the following procedure was followed: (1) a bilingual study team member performed an initial translation; (2) a bilingual community member edited the translation; (3) a certified medical translator edited the revision; (4) a focus group of N=5 bilingual community members made contextual edits; (5) a back-translation was performed; (6) an additional bilingual focus group examined the final version for compatibility; and (7) the medical translator certified the accuracy of the final version. T-tests examined differences between those who completed the measure in Mexican Spanish vs English. Results: Of the N=100 survey respondents, N=42 completed the BRISC in Spanish. No significant differences were seen in overall scores between those who completed the measure in English or Spanish (p=0.69). In addition, no differences were seen for individual items regarding time to bed (p=0.30), wake time (p=0.77), total sleep time (p=0.58), or sleep quality (p=0.98). Conclusion: Data collection instruments be linguistically and culturally appropriate to the study population. This version of the BRISC was adapted to Mexican Spanish for use in future studies. Support (If Any):